Assessing Early Warning Systems : How Have they Worked in Practice? - Berg, Andrew; Borensztein, Eduardo; Pattillo, Catherine (Washington, D.C. : International Monetary Fund, 2004)
Since 1999, the IMF's staff has been tracking several early-warning-system (EWS) models of currency crisis. The results have been mixed. One of the long-horizon models has performed well relative to pure guesswork and to available non-model-based forecasts, such as agency ratings and private analysts' currency crisis risk scores. The data do not speak clearly on the other long-horizon EWS model. The two short-horizon private sector models generally performed poorly.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet